Neuromodulation for Intractable Pain - Aziz, Tipu; Green, Alex (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Over 7% of the Western population suffers from intractable pain. Despite pharmacotherapy, many patients (1.5%) suffer from refractory pain. In addition to the pain, patients continue to be highly debilitated and suffer from depression and anxiety, poor quality of life and loss of employment. An ever enlarging global problem concerns the use of opiates which have risen to dangerous levels. Neuromodulation of the nervous system-where the function of the nervous system is altered by a device-has, over time, emerged as an effective alternative to pharmacotherapy in the management of these patients. In this Special Issue, we discussed the indications, safety, efficacy, mechanisms of action and other aspects of neurmodulation therapies for pain relief. These include peripheral nerve stimulation, peripheral field stimulation, spinal cord stimulation, dorsal root ganglion stimulation, motor cortex stimulation and deep brain stimulation. We do not intend this Special Issue to be a comprehensive study of pain but a guide to help clinicians to refer patients appropriately and to decide which procedure would best be offered in certain situations.